Transcrestal sinus lift with simultaneous implant placement using osseodensification in posterior maxilla with residual bone height of 4-6 mm - Elsaid, Mohammed Gamal Abdelftah Hamed; Aboelhasan, Mohsen Fawzy; Shuman, Mohammad Abd Elhamied; Alashmawy, Mohammed Mahgob Mohamed; Abdelrahman, Ahmed Omar Ahmed; Elwaseef, Safwat Saber Mohamed Mursey Ali (Brazilian Dental Science, 2022)
Objective: The aim of this study was to evaluate the transcrestal sinus lift using Osseodensification technique with simultaneous implant placement. Material and Methods: In this case series 7 patients who needed implant placement in the atrophic posterior maxilla were enrolled. In all the cases the residual bone height between the sinus floor and the alveolar crest was 4-6 mm. Transcrestal sinus lift was performed using Osseodensification with simultaneous implant placement. Cone-beam computed tomography (CBCT) were obtained immediately postoperative and 6 months after operation. Implant stability using Osstell® were assessed at the time of implant placement and implant exposure (6 months). Results: The results showed that the mean bone height gain was 5.33±0.83mm at 6 months postoperatively. Mean bone density value was 818.43±109.63 HU. Mean ISQ value was 80.00±3.11 at 6 months postoperatively. The duration of surgical procedure (minutes) ranged between 25-38 minutes with an average of 30.86±4.10 minutes. Conclusion: The crestal maxillary sinus floor elevation using Osseodensification technique with simultaneous implant placement provide superior results regarding bone density and implant stability and less duration of surgical procedure. KEYWORDS Sinus floor augmentation; Bone substitutes; Alveolar bone loss; Osteotomy; Dental implantation; Cone-beam computed tomography.